ERGONOMICS EDUCATION IN ORTHOPEDIC SURGERY - Joanna, Bartnicka; Alicia, Piedrabuena; Raquel, Portilla; Katarzyna, Mleczko; Luis, Moyano Juan; Blas, Pagador José; Sánchez-Margallo, Francisco M; Peter, Augat; Jarosław, Tokarczyk (LIFE: International Journal of Health and Life-Sciences, 2017)
The motivation of research was poor quality of working conditions in orthopedic practice which results from lack of use of ergonomics principles by medical staff. Hence, the research objective was to indicate the most important determinants for creating high-quality working conditions in operating room, particularly when performing orthopedic procedures. As methodology, the observations, video-registrations and interviews with orthopedic professionals were conducted. Based on the research material, the ergonomic and workflow assessments were examined. The research outcomes confirmed a problem of low quality working conditions during orthopedic surgeries resulted from insufficient knowledge and awareness of orthopedists regarding ergonomics. There was diagnosed a need for creation of a specialized guide for orthopedists and medical decision makers of how to improve working conditions in operating room on the background of the human and technical perspectives. As a result there was proposed the comprehensive online course on ergonomics for orthopedists and all medical staff who are interested in and are responsible for safety and comfortable conditions at their workplace. Hence the future scope is formulated as the monitoring and evaluation of working conditions after implementing ergonomics course within medical staff.